Percutaneous 60-day peripheral nerve stimulation implant provides sustained relief of chronic pain following amputation: 12-month follow-up of a randomized, double-blind, placebo-controlled trial. Issue 1 (17th November 2019) - Gilmore, Christopher A; Ilfeld, Brian M; Rosenow, Joshua M; Li, Sean; Desai, Mehul J; Hunter, Corey W; Rauck, Richard L; Nader, Antoun; Mak, John; Cohen, Steven P; Crosby, Nathan D; Boggs, Joseph W
Abstract : Introduction: Peripheral nerve stimulation (PNS) has historically been used to treat chronic pain, but generally requires implantation of a permanent system for sustained relief. A recent study found that a 60-day PNS treatment decreases post-amputation pain, and the current work investigates longer-term outcomes out to 12 months in the same cohort. Methods: As previously reported, 28 traumatic lower extremity amputees with residual and/or phantom limb pain were randomized to receive 8 weeks of PNS (group 1) or 4 weeks of placebo followed by a crossover 4 weeks of PNS (group 2). Percutaneous leads were implanted under ultrasound guidance targeting the femoral and sciatic nerves. During follow-up, changes in average pain and pain interference were assessed using the Brief Pain Inventory–Short Form and comparing with baseline. Results: Significantly more participants in group 1 reported ≥50% reductions in average weekly pain at 12 months (67%, 6/9) compared with group 2 at the end of the placebo period (0%, 0/14, p=0.001). Similarly, 56% (5/9) of participants in group 1 reported ≥50% reductions in pain interference at 12 months, compared with 2/13 (15%, p=0.074) in group 2 at crossover. Reductions in depression were also statistically significantly greater at 12 months in group 1 compared with group 2 at crossover. Conclusions: This work suggests that percutaneous PNS delivered over a 60-day period may provide significant carry-over effects including pain relief, potentially avoiding the need for a permanently implanted system while enabling improved function in patients with chronic pain. Trial registration number: NCT01996254 .